Justice in the Jury: The Benefits of Allowing Felons to Serve on Juries in Criminal Proceedings - Sharion Scott (Washington University Journal of Law & Policy, 2018)
This note by Sharion Scott highlights an often-ignored remnant of the old common law concept of civil death wherein a felony conviction carried with it the revocation of civil rights long after a sentence was served. Specifically, Scott points to the fact that thirty-one states exclude felons from serving on juries. Scott argues that where a disproportionate number of incarcerated people are black, the practice of excluding felons from jury duty perpetuates the underrepresentation of minorities on juries and exacerbates jury bias. Scott argues that jury service should be open to felony offenders who have completed their sentences and desire to civically engage with society and that criminal rehabilitation, civic participation, and jury integrity are best served by the inclusion of felons in the jury pool.
Keywords: civil death; felony conviction; sentencing; jury duty; jury pool; voir dire; discrimination; jury exclusion; minority defendants; prosecutorial discretion; prosecutorial bias; Sixth Amendment; conviction rates; Fourteenth Amendment; Batson; diversity; civic participation